The Quality Evaluation Method of Instrument Flight Procedure Design Scheme Based on Fuzzy Linguistic Assessments - Chen Ken (Institute of Advanced Engineering and Science, 2013)
The quality of Instrument Flight Procedure Design Scheme (QIFPDS) is directly related to the terminal area airspace capacity, quality, efficiency of air traffic management, and even the safety of aircraft. Hence, the evaluation of QIFPDS has great significance in real life. However, the evaluation of QIFPDS in real work is mainly done by experts through their specific knowledge and experience, which usually leads to a bias result and inevitably contains subjectivity and arbitrary defects. In this paper, a multi-attribute group decision-making method is proposed. This method makes full use of evaluation information; objectively and effectively evaluate QIFPDS. Also in this paper, a mathematical model for this method is introduced and a detailed step to solve this model is listed. At the end of this paper, an example is given to show the effectiveness and feasibility of the method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3687